Between Environmental Change and Neoliberalism: The Effects of Oil Palm Production on Livelihood Resilience. Issue 5 (4th May 2019) - Abrams, Jesse; Pischke, Erin C.; Mesa-Jurado, M. Azahara; Eastmond, Amarella; Silva, Chelsea A.; Moseley, Cassandra
Abstract: Rural communities worldwide are increasingly confronted with the simultaneous impacts of environmental change dynamics and processes of economic restructuring that diminish traditional sources of state support while shifting investments toward large-scale intensive production models. A key question in this context is how livelihoods are affected by these interacting forces of change and whether new production models can contribute to resilience at the household and community scales. Here we examine the impacts of oil palm production on marginal rural communities in Mexico that have experienced both the economic changes associated with neoliberal policy reforms and the dynamics of environmental change. We find that oil palm production can contribute to livelihood resilience when community members participate in its management and governance and when production is associated with state support, but that the kinds of neoliberal policies promoting oil palm expansion may exacerbate existing community vulnerabilities in the face of environmental change.